Analysis of Interest in Learning English Studying PKBM Rahmatunajah - Durotun Nasiha; Dini Hidayati (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study is to determine how interested package B students are in learning PKBM Rahmatunnajah. A descriptive qualitative technique with a case study method is used in this study. Residents studying package B, subject instructors, and PKBM manager Rahmatunnajah were among the participants. Techniques for gathering data through observation and interviews. The veracity of the data is checked utilizing triangulation and reflexivity during the thematic analysis. The findings show that residents enrolled in the package B program at PKBM Rahmatunnajah are influenced by the following factors: first, internal factors of learning residents, such as a dislike for English lessons and the belief that English lessons are difficult, the attention of students who are still studying English, and low learning outcomes for learning citizens. Second, external elements such as the teacher's teaching manner or style are still repetitive, and students seldom employ learning media when learning.